Morality dimensions with reflection on teaching process - Kolak, Ante (Array, 2011)
The paper deals with morality through tree dimensions making the theoretical subject of study. The first dimension refers to harmonious relations between individuals. The result of amorality are easily noticeable in the field, there is a high level of agreement among the authors regarding morality, while the mentioned statements can be confirmed by teaching practice. The second dimension deals with connecting and harmonizing wishes, a need and a striving within and individual himself, while the focus of the third dimension is the purpose of human existence. The two latter fields are of great importance for work with gifted students. Moral principles of an individual have great importance for the development of moral interpersonal relations, while in the case of the third dimension there are great disputes.